Yoga as Ethics of Self-Transformation in the Sivagama Text - Ida Bagus Putu Suamba (Jurnal Kajian Bali (Journal of Bali Studies), 2021)
This paper attempts to reveal yoga as an ethics of self-transformation in the ?iv?gama text of Ida Pêdanda Madé Sidêmên (1858–1984). As yoga pervades Balinese textual tradition, adaptation and development of teachings in the Indonesian archipelago show the creativity of the indigenous people. The ?iv?gama was analyzed via textual studies with data categorized to foreground concepts of yoga. The s?rgah (canto) 15, in particular, introduces various forms of yoga and sam?dhi for purifying body and mind. Each section describes how to perform a specific yoga, the attributes of the associated deity, and the benefit that can be reaped by the practice. One finding is that the cosmic function from a yogic perspective in the ?iv?gama text differs from the views of Upani?adic texts. The summaries from this study hope to contribute to efforts to understand the teachings of yoga that are available in Sanskrit-Old Javanese literature.